Myeloid‐derived suppressor cells: Bridging the gap between inflammation and pancreatic adenocarcinoma. (27th January 2021) - Sharma, Vinit; Aggarwal, Anjali; Jacob, Justin; Sahni, Daisy
Abstract: Pancreatic cancer has been identified as one of the deadliest malignancies because it remains asymptomatic and usually presents in the advanced stage. Tumour immune evasion is a well‐known mechanism of tumorigenesis in various forms of human malignancies. Chronic inflammation via complex networking of various inflammatory cytokines in the local tissue microenvironment dysregulates the immune system and support tumour development. Pro‐inflammatory mediators present in the tumour microenvironment increase the tumour burden by causing immune suppression through the generation of myeloid‐derived suppressor cells (MDSCs) and T regulatory cells. These cells, along‐with myofibroblasts, create a highly immunosuppressive and resistant tumour microenvironment and are thus considered as one of the culprits for the failure of anti‐cancer chemotherapies in pancreatic adenocarcinoma patients. Targeting these MDSCs using various combinatorial approaches might have the potential for abrogating the resistance and suppressive nature of the pancreatic tumour microenvironment. Therefore, there is more curiosity in studying the crosstalk of MDSCs with other immune cells during pathological conditions and the underlying mechanisms of immunosuppression in the current scenario. In this article, the possible role of MDSCs in inflammation‐mediated tumour progression of pancreatic adenocarcinoma has been discussed.